STRATEGIES TO IMPROVE PSYCHOLOGICAL WELL-BEING: GUIDANCE AND COUNSELING TEACHERS AS PROFESSIONAL HELPERS - Koswara Koswara; Nadia Aulia Nadhirah; Nandang Budiman (Universitas Pendidikan Indonesia, 2024)
Guidance and counseling teachers as professional helpers in schools should try to improve psychological well-being in themselves first before providing services to students, so that the services provided can run optimally. Thus, this study aims to identify and describe strategies that can be used to improve the psychological well-being of guidance and counseling teachers. Then in its implementation, this study used a systematic literature review method, with a population of published literature with a focus on discussions related to strategies to improve psychological well-being of guidance and counseling teachers as professional helpers at school. After conducting the research, the results show that the strategies that can be adopted by the guidance and counseling teachers to improve psychological well-being in themselves are by: (1) understanding all the concepts of psychological well-being; (2) Doing self-care; (3) Doing wisdom therapy, well-being therapy, art therapy; and (4) Shaping one's own happiness through career choices, seeking social support, and building self-regulation.